Revealing Willingness of Consumers to the Information Economy - Kandratsenka, Volha (Information & Media, 2012)
The current economic conditions, together with the highly developed information and communication technologies, provide business entities with a variety of opportunities to work with consumers. The article relates the experience in revealing the level of readiness of educational services consumers – students – to a meaningful and productive interaction with a higher education institution in an information economy. The author proposes a way of estimating such willingness and the aspiration to an independent search and analysis of information, basing on the results of the consumers’ questioning. Visualization of data, splitting the respondents into groups were applied in the study, as well as tools of the geometric mean and the Mann–Whitney U non-parametric statistical hypothesis test were used. Keywords: willingness to consume, information economy, management, competitive advantages. Vartotojų pasirengimo informacinei ekonomikai atskleidimas Volha Kandratsenka Santrauka Šiuolaikinės ekonomikos sąlygos kartu su aukštu komunikacijos ir informacijos technologijų lygiu suteikia verslo subjektams įvairių darbo su vartotojais galimybių. Straipsnyje apibrėžtas švietimo paslaugų vartotojų – studentų – pasirengimo lygis prasmingai ir efektyviai sąveikauti su aukščiausią išsilavinimą teikiančia institucija informacinės ekonomikos sąlygomis. Autorė pateikia tokio pasirengimo vertinimo būdą, taip pat identifikuoja siekį savarankiškai ieškoti ir analizuoti informaciją, atsižvelgiant į poreikių anketavimo rezultatus. Tyrimui buvo taikoma duomenų vizualizacija, respondentų grupavimas, panaudotas geometrinio vidurkio instrumentas ir neparametrinis statistinis Mann–Whitney U kriterijus.